Flow cytometric analysis of platelet cyclooxygenase-1 and -2 and surface glycoproteins in patients with immune thrombocytopenia and healthy individuals. (19th May 2017) - Rubak, Peter; Kristensen, Steen D.; Hvas, Anne-Mette
Abstract: Immature platelets may contain more platelet enzymes such as cyclooxygenase (COX)-1 and COX-2 than mature platelets. Patients with immune thrombocytopenia (ITP) have a higher fraction of immature platelets and can therefore be utilized as a biological model for investigating COX-1 and COX-2 platelet expression. The aims were to develop flow cytometric assays for platelet COX-1 and COX-2 and to investigate the COX-1 and COX-2 platelet expression, platelet turnover, and platelet glycoproteins in ITP patients ( n = 10) compared with healthy individuals ( n = 30). Platelet count and platelet turnover parameters (mean platelet volume (MPV), immature platelet fraction (IPF), and immature platelet count (IPC)) were measured by flow cytometry (Sysmex XE-5000). Platelet COX-1, COX-2, and the glycoproteins (GP)IIb, IX, Ib, Ia, and IIIa were all analyzed by flow cytometry (Navios) and expressed as median fluorescence intensity. COX analyses were performed in both whole blood and platelet rich plasma (PRP), whereas platelet glycoproteins were analyzed in whole blood only. ITP patients had significantly lower platelet count (55 × 10 9 /L) than healthy individuals (240 × 10 9 /L, p < 0.01), but a higher MPV ( p = 0.03) and IPF ( p < 0.01). IPC was similar for the two groups ( p = 0.74). PRP had significantly lower MPV ( p < 0.01) and significantly higher platelet count and IPC (both p -values <0.03) when compared with whole blood. IPF was similar for PRP and whole blood ( p = 0.18). COX-1 expression was 10 times higher and COX-2 expression was 50% higher in PRP than in whole blood (pCOX-1 < 0.01, pCOX-2 < 0.01). Platelet COX-1 expression was higher in ITP patients than healthy individuals using whole blood (pCOX-1 < 0.01) and PRP, though this was nonsignificant in PRP (pCOX-1 = 0.17). In ITP patients, positive correlations were found between platelet turnover and COX-1 expression (all p -values <0.01, rho = 0.80–0.94), whereas healthy individuals showed significant though weaker correlations between platelet turnover and COX-1 and COX-2 expressions (all p -values <0.03, rho = 0.44–0.71). GPIIb, IX, and Ib expression was increased in ITP patients compared with healthy individuals (all p -values < 0.03). GPIIb, IX, Ib, and IIIa showed positive correlations with platelet turnover in ITP patients (all p -values <0.02, rho = 0.71–0.94), but weak and nonsignificant correlations in healthy individuals (all p -values >0.14, rho = 0.11–0.28). In conclusion, ITP patients expressed higher COX-1 and platelet glycoprotein levels than healthy individuals. COX-1 and platelet glycoproteins demonstrated positive correlations with platelet turnover in ITP patients. In healthy individuals, COX-1 and COX-2 expression correlated positively with platelet turnover. PRP was more sensitive compared with whole blood as regards determination of COX. Therefore, PRP is the recommended matrix for investigating COX-1 and COX-2 in platelets.